Infusion monitoring strategies with wireless systems in infectious and dangerous diseases - Oktavia, Dian Putri; Saktioto, Saktioto; Hairi, Haryana Mohd; Asyana, Vepy (Science, Technology and Communication Journal, 2024)
Intravenous (IV) infusion therapy is a medical procedure that involves the insertion of fluids directly into the patient's vein using a needle/cannula. Mismanagement during infusion fluids replacement due to negligence and shortage of medical personnel and human error must be addressed promptly. Increasing in numbers of patients throughout the Covid-19 pandemic has raised the use of infusion and the error percentage in manual infusion monitoring has also escalated, as consequence, the needs of automatic-handy tools with affordable price become a concern. The infusion monitoring system used consists of three parts, namely sensing and computing, communication, and User. This device allows monitoring and visualization of IV therapy infusion for each patient in real-time, at a remote location.